Reconstruction of coronoid process of the ulna: a literature review - Zhao, Shanwen (J Int Med Res, 2021)
As a pivotal part of the elbow joint structure, the coronoid process of the ulna plays a vital role in maintaining elbow joint stability. Loss of coronoid process height causes instability of the elbow joint depending on the fracture characteristics and size. The diagnosis and treatment of coronoid process fractures has gained widespread attention from orthopedic surgeons. Nevertheless, few reports have described reconstruction of coronoid process fractures and defects that affect elbow joint stability. Treatment of elbow joint instability induced by coronoid process defects is challenging because most cases are complicated by other elbow joint injuries. Moreover, the clinical efficacy remains unclear. The present narrative review was performed to examine the research progress on reconstruction of the coronoid process. The findings of this review provide evidence for clinical repair and reconstruction of coronoid process defects and contribute to the published literature on this topic.